2015
DOI: 10.3390/ijms161125953
|View full text |Cite
|
Sign up to set email alerts
|

Betulinyl Sulfamates as Anticancer Agents and Radiosensitizers in Human Breast Cancer Cells

Abstract: Betulinic acid (BA), a natural compound of birch bark, is cytotoxic for many tumors. Recently, a betulinyl sulfamate was described that inhibits carbonic anhydrases (CA), such as CAIX, an attractive target for tumor-selective therapy strategies in hypoxic cancer cells. Data on combined CAIX inhibition with radiotherapy are rare. In the human breast cancer cell lines MDA-MB231 and MCF7, the effects of BA and betulinyl sulfamates on cellular and radiobiological behavior under normoxia and hypoxia were evaluated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 44 publications
4
14
0
Order By: Relevance
“…2 and 3). These effects are in line with previous reports that also demonstrated reductions in CA9 mRNA and CAIX protein level in tumor cells in response to treatment with RNA interference or CAI U104 (10,21,22,(34)(35)(36). CAI-induced changes were attributed to the possible degradation or internalization of CAIX (21,36).…”
Section: Caix Expression Under Different Cell Culture Conditionssupporting
confidence: 92%
See 4 more Smart Citations
“…2 and 3). These effects are in line with previous reports that also demonstrated reductions in CA9 mRNA and CAIX protein level in tumor cells in response to treatment with RNA interference or CAI U104 (10,21,22,(34)(35)(36). CAI-induced changes were attributed to the possible degradation or internalization of CAIX (21,36).…”
Section: Caix Expression Under Different Cell Culture Conditionssupporting
confidence: 92%
“…Initial studies of a colorectal carcinoma xenograft model revealed that CAIX inhibition with different CAIX inhibitors (CAI: Acetazolamide, DH348 or 11c) or CA9 knockdown by shRNA delayed tumor growth and radiosensitized tumor cells (16,17). These findings corroborate other studies showing that inhibition of carbonic anhydrases with different CAIs radiosensitized different tumor cell lines (21,35,42). This effect may be due to the reduced acidification of the extracellular environment (16,17) or the intracellular acidification ( Fig.…”
Section: Caix Expression Under Different Cell Culture Conditionssupporting
confidence: 84%
See 3 more Smart Citations